The Role Of Innovative Marketing In Enhancing Creativity Of Industrial Organizations - Ahmed Khalf , Ghfran; Mohammad Ali, Shifaa (Journal of Economics and Administrative Sciences, 2024)
Innovative marketing has become a basic pillar that countries and industrial companies rely on to achieve creativity in their work, a true criterion for their success and failure, and an essential element for their profit or loss. Innovative marketing has become an urgent necessity and there is no way to ignore it, because of its vital therefore, industrial organizations must shift from traditional marketing to innovative marketing and think outside traditional frameworks by constantly keeping pace with development, encouraging innovation, generating modern ideas, and adopting the concept of creativity by following modern and innovative marketing means and methods based on distinction and superiority. Hence, this search aimed to know the influence of innovative marketing in developing creativity. Data were collected using a questionnaire survey. The questionnaire form was distributed to a sample of 84 employees at the General Company for Textile and Leather Industry, in addition to personal interviews conducted by the researchers. The study results indicated that there is a relationship between innovative marketing in developing creativity through the selected dimensions, as the company’s management seeks to provide better sustainable programs for developing creativity by enhancing activities related to understanding customers’ desires and providing more of those desires. Paper type: Analytical research.